Role of PD-L1 in mediating the effect of lipid on ulcerative colitis: a mediation Mendelian randomization study - Li, Peihong; Wang, Yiwen; Hu, Hongyi; Sun, Boyun (Frontiers in Genetics, 2025)
IntroductionRecent evidence suggests that lipids play a crucial role in intestinal metabolic balance and are closely linked to ulcerative colitis (UC). However, the mechanisms underlying their effects remain unclear. This study employed Mendelian randomization (MR) to investigate the relationships among lipids, inflammatory factors, and UC.MethodsWe analyzed data on 179 lipids from the GeneRISK cohort (7,174 individuals), 91 inflammation-related proteins from the EBI GWAS Catalog (14,824 participants), and UC GWAS summary statistics from the FinnGen Biobank (411,317 samples). Associations were assessed using inverse variance weighted (IVW) and Bayesian-weighted MR (BWMR) methods. A mediation analysis was conducted to explore the potential role of inflammatory factors in mediating lipid effects on UC.ResultsMR analysis revealed a significant negative association between sterol ester (27:1/20:4) levels and UC (SNPs = 31; IVW: OR = 0.900 [95% CI: 0.851–0.952], p < 0.001; BWMR: OR = 0.906 [95% CI: 0.849–0.967], p = 0.003). Furthermore, sterol ester (27:1/20:4) was negatively correlated with PD-L1 (SNPs = 30; IVW: OR = 0.961 [95% CI: 0.934–0.990], p = 0.008), and PD-L1 was found to be inversely associated with UC (SNPs = 24; IVW: OR = 0.850 [95% CI: 0.724–0.999], p = 0.048). Mediation analysis suggested that sterol esters (27:1/20:4) may indirectly increase UC risk by downregulating PD-L1 expression. However, the MR analysis results suggest that sterol esters (27:1/20:4) act as a protective factor against UC, which contradicts the mediation analysis. This discrepancy highlights the dual role of PD-L1 in UC pathogenesis.DiscussionPD-L1 may serve as a key mediator in the regulation of UC pathogenesis by sterol esters, but the underlying complex mechanisms require further investigation.